HUBUNGAN ANTARA PERAN ORANG TUA DAN KOMPETENSI PEDAGOGIK GURU DENGAN HASIL BELAJAR MATEMATIKA - Amelia Diantami Adesta; Khasanah Khasanah (Akademika, 2022)
The purpose of this study was to determine the significant relationship between the role of parents and mathematics learning outcomes, the significant relationship between the teacher's pedagogic competence, and the significant relationship between the role of parents and the teacher's pedagogic competence together with the mathematics learning outcomes of sixth grade students in the city of Bekasi. The research method used in this research is survey method with correlation technique. The population used in this study is divided into two, namely, the target population and the affordable population. The target population comes from the sixth grade elementary school students in the city of Bekasi, while the accessible population is the sixth grade elementary school as many as 100 people. The samples in this study were students from Al Muzzammil Integrated Islamic Elementary School, Darul Maza Integrated Islamic Elementary School, Al Fajar Islamic Elementary School, and Ar Rahman Islamic Elementary School. In this study, the instrument used is a questionnaire and secondary data. The results of this study are first, the role of parents has a significant relationship with learning outcomes in mathematics. Second, teacher pedagogic competence has a significant relationship with mathematics learning outcomes. Third, the role of parents and the teacher's pedagogic competence together have a significant relationship with mathematics learning outcomes.